Research on fault localization of distribution transformers based on frequency response analysis and support vector machine (SVM) - Liu, Xingting; Wang, Haiqi; Gao, Zhuo; Han, Xutao (Frontiers in Energy Research, 2024)
Distribution transformers are vital to the stability of the power system, but long-term operation and environmental factors can cause distribution transformers to discharge, posing a potential threat. The impulse voltage withstand test rigorously evaluates the insulation of the transformer windings, to prevent accidents caused by insulation breakdown. However, due to the small size of distribution transformers, impulse voltage withstand test breakdown usually cause less damage, and it is challenging to locate the point of failure using traditional methods such as spatial positioning or disassembly. Therefore, the study of the discharge location method based on the characteristic value of the frequency response waveform is of great significance to find and deal with potential faults. This paper discusses the waveform characteristics of different discharge signals transmitted from different positions of the winding to the end. By analyzing the frequency response of different breakdown current signals measured at the end of the transformer winding, support vector machine is used to identify the breakdown position of the distribution transformer. The approximate location of the fault was identified with more than 80% accuracy. The feasibility and effectiveness of this localization method are verified by experiments.